POSTMODERNIST MOTIVES IN THE WORKS OF VAN ANI AND A. KEMELBAEVA - А.А. Кенжебaевa; Р.О. Досымбековa (Journal of Oriental Studies, 2019)
This article gives a comparative analysis of the work of Chinese writer Wang Ani and Kazakh writer Kemelbayeva in terms of artistic techniques for creating a double code, the features of the author’s speech and characters, the postmodern motive in the works of both writers. Also, differences in the methods for creating a framework of reality and fictitiousness in the stories of both writers were revealed. Key words: postmodernism, stream of consciousness, internal monologue, plot.